LEGAL MECHANISMS FOR IMPLEMENTING SCIENTIFIC RESEARCH INTO PRACTICE ON THE BASIS OF PUBLIC-PRIVATE PARTNERSHIP (Universal International Scientific Journal, 2026)
This article analyzes the legal mechanisms for implementing scientific research in public-private partnerships. The regulatory and legal framework of PPPs, contractual regulation, intellectual property rights, risk sharing, monitoring, and accountability institutions are considered from a scientific perspective.
Keywords: public-private partnership; scientific research; legal mechanism